Case report: successful treatment of membranous lupus nephritis with belimumab in an African female immigrant. Issue 6 (June 2016) - Scheerder, Marie-Angélique; Boey, O.; Mahieu, E.; Vanuytsel, J.; Bogaert, Anne-Marie
Abstract We describe the case of a 26-year-old African female who was treated successfully with belimumab in a case of severe membranous lupus nephritis and retinal vasculitis, resistant to first line therapy. She presented initially with chronic dacryoadenitis and screening showed nephrotic-range proteinuria. Biopsy of the kidney confirmed the diagnosis of membranous lupus nephritis. Clinical features (joint pain, dacryoadenitis, retinal vasculitis and lupus nephritis) in combination with serology (positive anti-double-stranded DNA (ds-DNA) antibodies, hypocomplementemia) confirmed the diagnosis of systemic lupus erythematosus (SLE). Treatment was immediately initiated with glucocorticosteroids (GCS), mycophenolate mofetil (MMF) and hydroxychloroquine sulphate (Plaquenil®). Tacrolimus was associated but no effect was observed with the proteinuria remaining in the nephrotic range and secondary effects of the glucocorticosteroids becoming a real concern. The patient was started on add-on belimumab with quasi-immediate effect on the proteinuria, making it possible to decrease the dosage of the other immunosuppressants and gradually stop them, even the GCS. The patient is currently in complete remission after 3 years of treatment with belimumab. We were able to stop immunosuppressive treatment but will keep her on antimalarial treatment as the most recent guidelines in treatment of SLE recommend.